Analysis of College Students' Consumption and Its Influencing Factors (Asian Business Research, 2022)
University is a special stage in life. As a special consumer group, the shaping and cultivation of college students' consumption concept has a more prominent and direct impact on the formation and development of their world outlook, and then has an important impact on people's life moral behavior. It is an effective way to describe college students' consumption in their daily life. In this paper, questionnaire survey, stratified sampling and other methods are used to investigate the consumption of college students, and multivariate statistical analysis is used to analyze the consumption structure.